2022
DOI: 10.1177/09722629211073278
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Job Insecurity on Work–Life Balance during COVID-19 in India

Abstract: The ongoing health crisis has impacted businesses worldwide, drastically reducing production, consumption and distribution of goods and services, leading to an economic downturn. An increasing unemployment rate has led to a surge in the sense of job insecurity among employees. Lack of job security has a direct impact on an employee’s health and work–life balance. This article focusses on the relationship between and impact of job insecurity on work–life balance, that is, to understand the impact of perceived j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Literature demonstrated that work organization conditions can influence job performance (Simard and Parent-Lamarche, 2021;Rawashdeh et al, 2022). They encompassed five work-related variables, which can affect job performance: workload (Bruggen, 2015;Parent-Lamarche and Boulet, 2021b); skill utilization and decision authority (Simard and Parent-Lamarche, 2021;Hackman and Oldham, 1980), as well as recognition Oldham, 1976, 1980;Ahmad et al, 2017;Bradler et al, 2016;Parent-Lamarche and Laforce, 2022), and job insecurity (Sverke et al, 2002;Kalia and Bhardwaj, 2019;Begum et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature demonstrated that work organization conditions can influence job performance (Simard and Parent-Lamarche, 2021;Rawashdeh et al, 2022). They encompassed five work-related variables, which can affect job performance: workload (Bruggen, 2015;Parent-Lamarche and Boulet, 2021b); skill utilization and decision authority (Simard and Parent-Lamarche, 2021;Hackman and Oldham, 1980), as well as recognition Oldham, 1976, 1980;Ahmad et al, 2017;Bradler et al, 2016;Parent-Lamarche and Laforce, 2022), and job insecurity (Sverke et al, 2002;Kalia and Bhardwaj, 2019;Begum et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…, 2016; Parent-Lamarche and Laforce, 2022), and job insecurity (Sverke et al. , 2002; Kalia and Bhardwaj, 2019; Begum et al. , 2022).…”
Section: Methodsmentioning
confidence: 99%
“…downsizing, restructuring and redundancy) led to loss of job control and security, which in turn exacerbated employees' psychological strain and emotional exhaustion (del Rio‐Chanona et al. 2020 ) and increased their work‐life conflict (Begum, Shafaghi and Adeel 2022 ). In April 2020, the International Labor Organization (ILO) estimated global unemployment to be 190 million, primarily driven by job losses in the food and accommodation, retail and wholesale and business services and administration sectors (Clarke 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ganson et al ( 2021 ) surveyed 4852 young adult workers in the United States and reported job loss for 2862 (59%) at the start of the pandemic in June 2020. Mckinsey's report on global diversity, equity, and inclusion claims that job insecurity increased to 78% in India owing to COVID‐19 (Begum et al, 2022 ). Employees experiencing a fall in their income levels would curtail their consumption expenditure.…”
Section: Results and Findingsmentioning
confidence: 99%